2006
DOI: 10.1606/1044-3894.3549
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Functional Improvement over Time in a System of Care

Abstract: troul and Friedman (1986) defined a system of care as "a comprehensive spectrum of mental health and other necessary services which are organized into a coordinated network to meet the multiple and changing needs of children and families." During the past 2 decades, the system of care movement has brought about the creation of a variety of innovative approaches to service provision for young people involved in multiple child-serving systems (e.g., mental health, child welfare, juvenile justice, education) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It could also be that involvement of a large percentage of adolescents in the juvenile justice system indicated that these adolescents might have been in the traditional mental health system for a significant amount of time and had had poor responses to treatment. Previous studies suggest that exposure to a deficit-based treatment approach requires a considerable amount of time to undo psychological damage (or hardening) from previous unsuccessful approaches and to allow the adolescents and their families to trust the strengths-based system and have hope that the system can help them succeed (Anderson et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It could also be that involvement of a large percentage of adolescents in the juvenile justice system indicated that these adolescents might have been in the traditional mental health system for a significant amount of time and had had poor responses to treatment. Previous studies suggest that exposure to a deficit-based treatment approach requires a considerable amount of time to undo psychological damage (or hardening) from previous unsuccessful approaches and to allow the adolescents and their families to trust the strengths-based system and have hope that the system can help them succeed (Anderson et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…This age group was selected because studies show a doubling of the prevalence of SED, including disruptive disorders, between ages 12 and 13 years (Arnold, Walsh, Oldham, & Rapp, 2007; Costello et al, 1996), with significant functional impairment noted about the age of 12 years (Costello et al, 1996). The average length of involvement in the Dawn Project was 14 months (Anderson et al, 2006). The 12-month end time point was chosen because it was close to the average point at which participants exited treatment and thus provided the best opportunity to examine relationships of interest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these are related to our analysis. Anderson et al (2006) found that demographic characteristics, referral source, Medicaid status, presenting problems, or place of residence (i.e., facility) did not predict improvement over time in a SOC. Only baseline age predicted functional improvement after six months of SOC involvement—Younger youth tended to improve, whereas older youth tended to deteriorate.…”
Section: Introductionmentioning
confidence: 90%
“…Studies of other SOC communities have been published to date (Anderson et al 2006; Anderson et al 2007; Barksdale, Azur, and Daniels 2010; Barksdale, Azur, and Leaf 2009; Cook and Kilmer 2010; Gyamfi, Keens-Douglas, and Medin 2007; Miech et al 2008), among others. Three of these are related to our analysis.…”
Section: Introductionmentioning
confidence: 99%